Transition metal qubits in 4H-silicon carbide : a correlated EPR and DFT study of the spin S=1 vanadium V3+ center - von Bardeleben, H. J. (2021)
Whereas intrinsic defects in silicon carbide (SiC) have been widely considered for qubit applications, transition metals in this material have not yet been recognized as alternative systems. We have investigated the magneto-optical properties of the V3+ center in 4H-SiC by electron paramagnetic resonance (EPR) and photo-EPR spectroscopy in view of their possible application in quantum technology. We show that they fulfill all the requirements for such applications: a high-spin S=1 ground state, optically induced ground-state spin polarization of more than 70%, long spin-lattice relaxation times of the order of a second, as well as associated zero-phonon photoluminescence emission lines in the range of 1.8 μm. Further, the zero-field splitting parameter D is temperature dependent and increases between T=4K and T=292K linearly with a rate of 440 kHz/K, allowing potential nanoscale temperature sensing. These properties make the vanadium acceptor an extremely promising candidate for qubit applications with optical properties in the telecommunication optical range.